2007
DOI: 10.1021/ic701461b
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Complexes Possessing N2O2S2-Based Ligands:  Highly Active Procatalysts for the Homopolymerization of Ethylene and Copolymerization of Ethylene/1-hexene

Abstract: The family of ligands containing an N2O2S2 core, namely, 1,2-di(3-Me-5-t-Bu-salicylaldimino-o-phenylthio)ethane (H2L1), 1,3-di(3-Me-5-t-Bu-salicylaldimino-o-phenylthio)propane (H2L2), 1,4-di(3-Me-5-t-Bu-salicylaldimino-o-phenylthio)butane (H2L3), and 1,2-di(3-Me-5-t-Bu-salicylaldamino-o-phenylthio)ethane (H2L4), have been prepared and complexed with a variety of vanadium chlorides and alkoxides to afford complexes of the form [V(X)L1] (X = O (1), Np-tol (2), Cl (3)), [V(O)(L2,3)] (L2 (4), L3 (5)), and [V(L4)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Increasing ligands denticity seems to be an efficient method to stabilize the active species of vanadium catalyst, which produced high molecular weights polymers with high catalytic activities 11–24. For example, Redshaw and coworkers reported that vanadium complexes with calixarene ligands exhibited excellent performance in olefin polymerization catalysis,11–16 Gibson and coworkers found tridentate bis(benzimidazole) amine ligand can stabilize the vanadium complexes that exhibited high activity toward ethylene (co)polymerization 17–19. Our group have synthesized and characterized a series of vanadium(V) complexes bearing tetradentate trihydroxy amine ligands, which exhibit high catalytic activities for the copolymerization of ethylene with some polar norbornene derivatives 20.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing ligands denticity seems to be an efficient method to stabilize the active species of vanadium catalyst, which produced high molecular weights polymers with high catalytic activities 11–24. For example, Redshaw and coworkers reported that vanadium complexes with calixarene ligands exhibited excellent performance in olefin polymerization catalysis,11–16 Gibson and coworkers found tridentate bis(benzimidazole) amine ligand can stabilize the vanadium complexes that exhibited high activity toward ethylene (co)polymerization 17–19. Our group have synthesized and characterized a series of vanadium(V) complexes bearing tetradentate trihydroxy amine ligands, which exhibit high catalytic activities for the copolymerization of ethylene with some polar norbornene derivatives 20.…”
Section: Introductionmentioning
confidence: 99%
“…2 that the molecular weight of polyethylene obtained with [VO(acacen)]/EtAlCl 2 is much higher than that for copolymers, and that it decreases with the increase of comonomer concentration in the feed. Such effects were observed repeatedly for copolymerizations catalyzed by different catalytic systems [21,[35][36][37][38]. Lower molecular weights of polymers for increasing 1-octene concentrations may result from the chain transfer to comonomer and/or more favourable β-hydride elimination after comonomer incorporation.…”
Section: Resultsmentioning
confidence: 67%
“…The information is also vital that the majority of vanadium complexes shows a better activity in combination with simple alkylaluminium compounds, especially EtAlCl 2 and Et 2 AlCl [10,[12][13][14][15][16][17][18]21], which makes them good alternatives for MAO activated zirconium and titanium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…et al reported that either VOCl3/Et3Al2Cl3 or VO(OtBu)3/Et3Al2Cl3 showed high cyclic dienes incorporation ability in the terpolymerization with ethylene and propylene [23]. Since the vanadium catalysts might be deactivated during the polymerization because of the reduction to low-valent, inactive species [27], introduction of bulky and polydentate ancillary ligands to stabilize active vanadium(V) species has been proven to be an effective approach to keep vanadium at high-oxidation and subsequently prolong the catalytic lifetime [28][29][30][31][32][33][34][35][36]. In our previous work, the synthesized [ONNO]-type and [ONN]-type oxovanadium(V) complexes also showed high catalytic activities and promising stabilities in copolymerization of ethylene with norbornene (NBE), and produced E/NBE copolymers with high NBE contents [37,38].…”
Section: Introductionmentioning
confidence: 99%